1997
DOI: 10.1590/s0103-84781997000200020
|View full text |Cite
|
Sign up to set email alerts
|

Identificação e prevalência de nematódeos do pacu Piaractus mesopotamicus (Holmberg, 1887), da estação de piscicultura do cepta, Pirassununga, SP, Brasil

Abstract: O trabalho foi realizado no Laboratório de Ictiopatologia do Departamento de Zootecnia da Universidade Federal de Santa Maria e no CEPTA, Município de Pirassununga, SP. Foram necropsiados 90 pacus que estavam em viveiros de criação da Estação de Piscicultura do CEPTA, com a finalidade de identificar os nematódeos presentes no tubo intestinal e observar a prevalência destes nos peixes. Foram coletados em três épocas do ano: verão, outono e primavera. Os nematódeos foram identificados como sendo todos pertencent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
1
1
0
3
Order By: Relevance
“…Prevalence data of R. rondoni observed in this study are close to the data reported by Parra et al (1997), who found 71% prevalence of this parasite in farmed P. mesopotamicus. In this study, R. rondoni practically obstructed the light in the intestine of the hosts, a fact that has already been reported by Rego and Vicente (1988) for the same host collected in the Paraguai and Miranda rivers.…”
Section: Discussionsupporting
confidence: 90%
“…Prevalence data of R. rondoni observed in this study are close to the data reported by Parra et al (1997), who found 71% prevalence of this parasite in farmed P. mesopotamicus. In this study, R. rondoni practically obstructed the light in the intestine of the hosts, a fact that has already been reported by Rego and Vicente (1988) for the same host collected in the Paraguai and Miranda rivers.…”
Section: Discussionsupporting
confidence: 90%
“…Its type species, Spectatus spectatus, has been reported mainly from serrasalmid fishes (Serrasalmidae) and, less frequently, parasitizing fishes of the families Bryconidae, Doradidae and Pimelodidae, in the Paraná River basin in Brazil and Argentina (Travassos, 1923;Travassos and Kohn, 1965;Hamann, 1982aHamann, , 1982bMasi Palláres, 1990;Parra et al, 1997;Moravec, 1998;Santos et al, 2003;Campos et al, 2009). Despite its widespread occurrence, the morphology of S. spectatus is not sufficiently known which has generated problems to separate Spectatus from 2 other kathlaniid genera, Falcaustra Lane, 1915 andChabaudinema Díaz-Ungría, 1968 (see Baker, 1980).…”
mentioning
confidence: 99%
“…Estes resultados corroboram as observações de Thatcher (1991) que R. rondoni não seria responsável por alterações teciduais no hospedeiro, mantendo uma relação de comensalismo. Martins & Urbinati (1993) observaram ausência de danos significativos, mesmo em grande número, mas Parra et al (1997) alertam sobre a possibilidade de obstrução intestinal pela elevada intensidade média. Campos et al (2009) observaram que R. rondoni praticamente obstruíram a luz do intestino de P. mesopotamicus, mas não notaram nenhum dano ao hospedeiro.…”
Section: Discussionunclassified
“…A prevalência e intensidade de infecção variaram em relação aos meses de coleta, observando-se ainda que nos meses de prevalência maior, a intensidade de infecção era menor. Parra et al (1997) também observaram diferença na prevalência em relação a diferentes épocas de coleta.…”
Section: Discussionunclassified
See 1 more Smart Citation